FARMERS' PERCEPTION OF THE COOPERATION SYSTEM WITH PT INDOFOOD IN POTATO FARMING IN SERANG VILLAGE, KARANGREJA, PURBALINGGA REGENCY - Kurniawati, Dwi Kurniawati; Djuharyanto, Teguh; Sitanini, Ayu (Jurnal Hexagro, 2025)
Perception is a person’s perspective on what they see, feel, and hear. This research aims to analyze farmers' perceptions of the cooperation system with PT Indofood in potato farming, which are still negative and which are already positive. This research was carried out in Serang Village, Karangreja District, Purbalingga Regency, from March 2024 to April 2024 using a purposive sampling technique with 32 respondents selected based on the criteria of potato farmers who had collaborated for two years and planted potatoes at the beginning of the potato planting season. The method used in this research is qualitative data, which is quantified using data analysis techniques using Likert's Summated Ratings method. The research results show that potato farmers' perceptions of the cooperation system with PT Indofood are in the good category, which is formed by perceptions of good seed availability and perceptions of good market guarantees.